Implementation of differentiated learning in elementary schools - Faigawati Faigawati; Mazda Leva Okta Safitri; Faradita Dwi Indriani; Fairus Sabrina; Kinanti Kinanti; Halim Mursid; Apit Fathurohman (Jurnal Inspirasi Pendidikan, 2023)
The Merdeka curriculum is intended so that students are free in carrying out their development in learning activities. The purpose of this study is to find out how the implementation of differentiated learning has been carried out by teachers in elementary schools. This study uses a descriptive qualitative approach using the Miles and Huberman model. Diagnostic assessment is in the form of short questions that can be written down or in the form of questions directly before starting learning. The characteristics of students who need differentiated learning are students who have diverse learning styles. Differentiation content is reading material, pictures, and learning videos related to the subject matter. Facilities that support differentiated learning are the availability of complete facilities and infrastructure. Evaluation of different product results, namely by referring to learning objectives. The most appropriate differentiated learning model is the PJBL/PBL learning model. ideally, the number of students in differentiated learning is between 10-25 students. An effective and constructive learning environment greatly influences the process of developing the quality of teachers and students in the school environment. To maximize student learning outcomes in differentiated learning, teachers need to collaborate with the parents of students. An indicator of the success of this differentiated learning is when students can express a sense of comfort through being active, changing good behavior, and increasing significant learning outcomes.